Puraṭcivīrar pārisṭar Makariṣi Śrī Va. Vē. Sū. Aiyar eḻutiya Kāviya uttiyāṉam : Śri Aiyar carittira curukkamum aṭaṅkiyatu - Aiyar, V. V. S. (Śrī Va. Vē. Su. Aiyar Ilakkiyam, 1980)
Article on epic literature, previously published in Pālapārati, Tamil monthly, in 1924; includes author's brief biography.